A review of research on adakites. Issue 1 (2nd January 2021) - Zhang, Lingyu; Li, Shichao; Zhao, Qingying
ABSTRACT: Taking account of their importance in inferring continental geodynamic processes, adakites have been the subject of considerable research since their discovery and identification. With their high Sr and low Y and HREE concentrations and high Sr/Y and La/Yb ratios, adakites were originally considered to be the product of slab melting in subduction zone settings. Adakites were therefore interpreted to yield information pertaining to magmatic processes, the mineralization of economic deposits, and crustal evolution along convergent margins. However, as more 'adakites' are reported, the lack of standardization of the term is becoming more apparent. The uncertainty of the nomenclature mainly evolves from the breadth of lithological definitions and the diversity of proposed adakite genesis. This paper reviews progress on the definition of adakites and related concepts, and formally introduces widely used classifications and genetic models. Using an adakite database compiled from published articles, 979 samples termed as adakites in the database were screened using a number of geochemical definitions, and 356 fully conforming rocks (termed reference adakite samples) were obtained. By comparing and analysing the characteristics of the reference adakite samples, we recognize that: (1) the screened reference adakites have enlightened the origin of anomalous samples; (2) the domain range of the reference adakites in compositional diagrams mainly supports the hypothesis that high-SiO2 adakites are consistent with the original definition of adakites; and (3) numerous genetic models can explain the formation of compositionally heterogeneous adakites, and therefore the use of the term adakite requires caution in their geodynamic interpretation. The reference adakite samples are also used to discuss the applicability of existing geochemical diagrams. There have also been developments in our understanding of the relationship between adakites and porphyry-type Cu–Mo–Au mineralization, which can be quantitatively assessed by constraining the relative oxygen fugacity. Graphical Abstract: uf0001